Dysaphis (Dysaphis) kadyrovi sp. nov.—a new aphid species (Hemiptera: Aphididae) from Tajikistan - Depa, Łukasz; Kanturski, Mariusz; Taszakowski, Artur; Walczak, Marcin; Taszakowski, Artur; Walczak, Marcin; Bugaj-Nawrocka, Agnieszka; Wieczorek, Karina (Zootaxa, 2017)
Dysaphis (Dysaphis) kadyrovi Depa & Kanturski sp. nov., a new aphid species associated with an endemic plant species Anacantha darwasica (C. Winkl.) Soják (Asteraceae) is described and figured from specimens collected in Tajikistan. Taxonomic comments on the morphological resemblance of the new species to closely related Dysaphis (D.) pseudomolli Narzikulov is provided. In view of the finding that the new species shares identical COI sequence with that reported for the morphologically distinct Dysaphis (Dysaphis) lappae lappae (Koch), the reliability of barcoding and molecular data is discussed.